2019
DOI: 10.1177/0300060518822404
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of PCT and CRP evaluation for adult ICU patients with sepsis and septic shock: retrospective analysis of 59 cases

Abstract: Objective To investigate the prognostic significance of serum procalcitonin (PCT) and C-reactive protein (CRP) in patients with sepsis and those with septic shock. Methods Fifty-nine patients were divided into sepsis and septic shock groups, as well as survivor and non-survivor groups, according to the severity of the disease and patient survival. Serum PCT and CRP measurements at the time of hospitalization in the intensive care unit were examined. Results On the 2nd, 3rd, and 5th days, the CRP level was high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 20 publications
2
59
4
Order By: Relevance
“…Otherwise, CRP is a well-known parameter for diagnosis of sepsis or assessment of predictor of successful antibiotic therapy [18,19]. Recent study indicated that on the 2 nd , 3 rd , and 5 th days, serum CRP level was higher in the nonsurvivor group than in the survivor group, and serum CRP has good clinical prognostic value for patients with sepsis and septic shock [20]. Inconsistently, there was no significant difference in aspect of CRP level on PICU admission between nonsurvivors and survivors in the present study.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…Otherwise, CRP is a well-known parameter for diagnosis of sepsis or assessment of predictor of successful antibiotic therapy [18,19]. Recent study indicated that on the 2 nd , 3 rd , and 5 th days, serum CRP level was higher in the nonsurvivor group than in the survivor group, and serum CRP has good clinical prognostic value for patients with sepsis and septic shock [20]. Inconsistently, there was no significant difference in aspect of CRP level on PICU admission between nonsurvivors and survivors in the present study.…”
Section: Mediators Of Inflammationmentioning
confidence: 99%
“…Several common inflammation biomarkers including c-reactive protein, procalcitonin, and white blood cell count have shown prognostic values on sepsis. 3,4 Early identification of those who are in danger of adverse outcomes might be conducive to prompt and adequate treatments of sepsis. 5 Complete blood count (CBC) is one of the most common and inexpensive laboratory tests in the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Serum PCT and CRP have good clinical diagnosis and prognostic value for patients with sepsis and septic shock. Kinetic studies of PCT and CRP may increase sensitivity and accuracy when evaluating the prognosis of patients with sepsis and septic shock [28]. They have been used for early detection of infection and directing antibiotic therapy [8].…”
Section: Discussionmentioning
confidence: 99%